Project-Based Learning in Interdisciplinary Spaces: A Case Study in Norway and the United States - Margaret Ann Bolick; Malena Thomassen; Jennifer Apland; Olivia Spencer; Fantasi Nicole; Sonja Kim Ngan Tran; Matthew Voigt; Kelly Best Lazar (Education Sciences, 2024)
The research described in this case study features a cohort of five exchange students from post-secondary institutions in Norway and the United States who collaboratively engaged in a project-based learning experience infused with aspects of place-based education, lesson study, and the pedagogical technique “students as partners”. The students were tasked with crafting an interdisciplinary lesson combining mathematics and environmental science to address a localized problem in the Southeastern United States. This study reflects on how the students participated in project-based learning as well as the instructional practices that supported student engagement. Students identified an increase in understanding of interdisciplinary and multicultural Science, Technology, Engineering, and Mathematics (STEM) education, a broader understanding of instructional practices, and exposure to educational research. Data were collected throughout the study using a variety of techniques, including discussion posts, collaborative documents, and reflections to gauge student experience and project progress. The results provide evidence to support the use of project-based learning in postsecondary STEM classrooms and emphasize the benefits of engaging students in curriculum development.